PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO DISERTAI KUIS DALAM PEMBELAJARAN BIOLOGI - Irdinansyah, Irdinansyah; Haviz, M.; Delfita, Rina (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research was to see the students biology learning outcome toward the aplication of active learning strategy type the power of two which included quiz. This research was an experimental research with design randomized control group posttest only design. The instrument of the research was posttest. Then, the data were analyzed by using t-test. The result of the research shown that there were differences of mean scores, standard deviation and varians between experiment class and control class. Finally, the result of this research indicatedÂ that the students biology learning outcome which applied the power of two strategy in experiment class was much better than control class.Keywords: learning type the power of two, quiz, biology learning